Integration of Artificial Intelligence in Islamic Education: Trends, Methods, and Challenges in the Digital Era - Salim, M Agus; Aditya, Riska Bayu (Journal of Modern Islamic Studies and Civilization, 2025)
This study employs a qualitative descriptive approach with a literature review method to analyze the application of Artificial Intelligence (AI) in Islamic education. Data were collected from 26 scholarly articles obtained through a systematic search in the SINTA database (1–6) and international journals (Q1–Q4), using keywords related to AI in Islamic education. Articles were selected based on their relevance to the research topic. Data analysis was conducted using descriptive analysis to identify AI usage trends and content analysis to evaluate key topics and challenges. The findings reveal a significant increase in AI usage since 2018, with descriptive analysis being the most commonly applied method. Key topics include AI integration in Qur'an and Hadith learning, the development of AI-based educational media, and the digitalization of Islamic manuscripts. Major challenges involve technological infrastructure limitations, ethical considerations, cultural sensitivities, and technological disparities between urban and rural areas.